No judge, no job!: Judicial discretion and incomplete labor contracts - Robin Christmann (Hamburgisches WeltWirtschaftsInstitut (HWWI), 2010)
The decision making of judges is prone to error and misapprehension. Consequently, the prevailing literature ties the economic function of courts to dispute resolution and minimization of rule making costs. In contrast to previous research, this analysis applies a contract theoretic perspective to the ruling of courts and keeps the focus on the implemented market transactions. Using labor contracts as institutional setting, performance and limitations of judicial law making are formally investigated and compared to the effects of specific legislation. It is shown that the efficient relation of legislative law making and judicial discretion is defined by the characteristics of the particular field of law and the actual market structure. The model also suggests a mutual dependency between legislation and adjudication to establish efficiency in law, contradicting the traditional legal doctrines of exclusive legislation or sole case-law.
Keywords: K12; K31; K41; 330; incomplete contracts; judicial law making; legislation